Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1071/ea9960209
|View full text |Cite
|
Sign up to set email alerts
|

Growth, yield and neurotoxin (ODAP) concentration of three Lathyrus species in mediterranean-type environments of Western Australia

Abstract: The growth, phenology, grain yield and neurotoxin (ODAP) content of Lathyrus sativus, L. cicera and L. ochrus were compared with a locally adapted field pea (Pisum sativum L.) to examine their potential as grain legumes in Western Australian farming systems. About 17 lines of each species were obtained from ICARDA, Syria, and grown at 3 agro-climatically different sites. In general, the 3 species were later flowering than field pea, especially L. cicera and L. ochrus; however, L. sativus was the last species t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 17 publications
4
26
1
Order By: Relevance
“…In our studies, L. cicera accessions as compared to grass pea, were characterized by a narrow range of pod number per plant (20.8-45.0) but markedly higher seed number per pod with a mean 2.3 versus 4.1 for grass pea and red pea, respectively. The Hanbury et al (1995) researches performed in Australia demonstrated that yield of L. cicera was generally much higher than of either L. sativus or L. ochrus and the promising lines of those species with high yielding and low b-ODAP were selected (Siddique et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our studies, L. cicera accessions as compared to grass pea, were characterized by a narrow range of pod number per plant (20.8-45.0) but markedly higher seed number per pod with a mean 2.3 versus 4.1 for grass pea and red pea, respectively. The Hanbury et al (1995) researches performed in Australia demonstrated that yield of L. cicera was generally much higher than of either L. sativus or L. ochrus and the promising lines of those species with high yielding and low b-ODAP were selected (Siddique et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It is distributed in the Mediterranean basin countries (from Portugal to Italy, Balkan countries and the Crime, Crete, Aegean Isles, Cyprus, Syria, Lebanon, Palestine, Jordan, Turkey, Egypt, Morocco, Algeria, Tunisia), Caucasus, Iraq, Iran, Central Asia (Turkmenia to Pamir-Altai), and introduced into South Africa (IPGRI 2000). Hanbury et al (1995) and Siddique et al (1996) reported L. cicera to show very good adaptation to arid land in South Australia as a potentially high yielding feed grain/forage crop. Yield of Lathyrus cicera was generally much higher than that of L. sativus and the lines with both high yield and low ODAP have been identified (Hanbury et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Siddique et al [28] indicated that the interaction between genotype and environment was minimal, but environment effects were large consideration for the variation in β-ODAP concentrations.…”
Section: Calibration Curvesmentioning
confidence: 99%
“…Several Lathyrus species and in particular Lathyrus sativus (grass pea) have great potential as alternative pulses in many cropping systems around the world (Siddique et al, 1996). From a respectful funeral offering, in the ancient pyramids of Egypt (Mitchell, 1971), and a reputed aphrodisiac for which it received its scientific name (over the stamina generating food of the Bangladeshi land labourers), to end up banned from the food basket in Europe, India and Nepal because of its toxicity, grass pea had a very tumultuous history.…”
Section: Introductionmentioning
confidence: 99%